2008
DOI: 10.3354/ab00072
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of rocky intertidal grazers: population status and potential impacts on community structure and functioning

Abstract: A wide range of anthropogenic activities are impacting the ecology of coastal areas. Exploitation of marine resources is one such activity, which, through cascading trophic effects, can have influences well beyond that of the target species. We investigated the mid-rocky-shore community structure of the Azores archipelago, a seldom-studied habitat, where there is a local tradition of exploiting limpets, the main intertidal grazers. The limpet population structure differed among islands, and there was an invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 31 publications
1
69
1
Order By: Relevance
“…Both species inhabit the intertidal rocky shore of the Canary Islands, achieving maximum population densities in the mid-shore range (Hawkins et al 1990, Martins et al 2008. However, our results suggest that P. ulyssiponensis is generally more abundant than P. candei crenata in intertidal habitats.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Both species inhabit the intertidal rocky shore of the Canary Islands, achieving maximum population densities in the mid-shore range (Hawkins et al 1990, Martins et al 2008. However, our results suggest that P. ulyssiponensis is generally more abundant than P. candei crenata in intertidal habitats.…”
Section: Discussioncontrasting
confidence: 57%
“…Oceanic island environments may be more susceptible to removal of these megaspawners owing to a higher isolation of populations, which may render island populations more vulnerable to exploitation than elsewhere (Roberts and Hawkins 1999). Over time populations are being progressively 'fished down' (Moreno 2001, Martins et al 2008, causing severe changes in population structure and an overall reduction in the density and size frequency of the resource. Previous studies in the Canary Islands have shown that intense exploitation of intertidal limpets leads to a dramatic reduction, and even local extinction, of populations of P. candei crenata (Côrte-Real et al 1996, Navarro et al 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1c), no significant effect of seawall modification was found (Table S2, see Supplementary material). The mean limpet biomass per plot (dry body weight estimated for each individual from an established length-mass relationship; see Martins et al 2008) of P. candei was also approximately five times greater (mean limpet biomass in mg ± SE, control: 38.2 ± 17.2, enhanced areas: 182.9 ± 30.4) in enhanced areas of the seawall. When considering the entire grazing assemblage (all species together), there was, on average, a significantly greater number of grazers in enhanced areas of the seawall than in unmanipulated controls (Fig.…”
Section: Enhanced Versus Control Areasmentioning
confidence: 97%
“…Across that region, Patellid limpets represent an important socioeconomic resource and have likely been exploited since the islands were first colonized (Hawkins et al, 2000), which, in the case of Canaries, goes back to around the middle of the 1st millennium B.C.E with recognized effects on the abundance of P. candei, at least in one island of the archipelago (Gonzalez-Lorenzo et al, 2015) (the human colonization of the Azores and Madeira goes back to the 15th century). The high levels of exploitation have contributed to severe declines in limpet abundance with many populations considered to be overexploited (Martins et al, 2008). The reductions in limpet abundance is also reported to be altering ecosystem services of the coastal areas, as it has been linked to the increase in turf-forming algae (Martins et al, 2010).…”
Section: Introductionmentioning
confidence: 99%